THE INTERRELATIONSHIP BETWEEN THE ORAL MICROBIOME AND RHEUMATOID ARTHRITIS: EXPLORING MUTUAL INFLUENCES AND CLINICAL IMPLICATIONS - Hanna Adamska; Natalia Klepacz; Marta Kaus; Karina Grzesik; Hubert Sawczuk; Katarzyna Pilarczyk; Weronika Ewa Nowak; Aleksandra Rabęda; Marta Malicka; Zuzanna Cudziło (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and objective: Periodontitis (PD) is caused by dysbiosis of the oral microbiome (OMB). The prevalence of PD is increased in RA patients. Both conditions  have the ability to activate common inflammatory pathways. The OMB shift contributes to more severe course of PD and RA. This paper aims to summarize the impact of OMB on chronic inflammation in the pathogenesis of PD and RA.Description of the state of knowledge: The OMB can influence chronic inflammation and protein citrullination. The presence of antibodies against citrullinated peptides (ACPA) correlates with an increased incidence and severity of periodontitis. While numerous studies have reported a relationship between the OMB, PD and RA, the role of specific bacteria in RA remains unclear.Methodology: A literature review was conducted using two databases - PubMed and Google Scholar - with search terms such as "oral microbiome”, “rheumatoid arthritis", "periodontal health”, “oral microbiota”, “periodontal disease”. Articles published within the last eight years were prioritized.Conclusions: PD is more prevalent and severe particularly in ACPA-positive RA patients. Alterations in OMB are associated with systemic inflammation, contributing to RA progression. and worsening periodontal conditions. Periodontal treatment shows a potential to reduce RA activity, emphasizing the importance of dental care in RA. Anti-inflammatory treatments may restore oral homeostasis. Targeting the OMB offers a potential for managing RA and PD. Further research is needed to establish guidelines for personalized therapies and prophylaxis.